Analysis of Factors That Influence Adherence to Taking Medication in Elderly People with Hypertension in the Working Area of Pakpak Bharat District - Sulastri Berutu; Nur'aini Nur'aini; Ramadhani Syafitri (The International Science of Health Journal, 2025)
Hypertension is still a health problem that must be followed up, World Health Organization (WHO) data in 2022 estimates that currently the global prevalence of hypertension is 22% of the total world population. Meanwhile, the hypertension report at the Salak Health Center in 2021 was 275 cases, in 2022 there were 324 cases, in 2023 there were 397 cases. Objective research to analyze the factors that influence adherence to taking medication in elderly people with hypertension in the Working Area of ??the Salak Health Center, Salak District, Pakpak Bharat Regency. The research design used Analytical Survey method with Cross Sectional approach. The population in this study were all patients The population in this study were all elderly hypertensive patients in the Salak Health Center Working Area, namely 73 patients who were all made into research samples with total population techniques. Data analysis used univariate analysis, bivariate with chi-square test and multivariate with logistic regression. The results of logistic regression research show that there is an influence of knowledge p = 0.014, motivation p = 0.006, family support p = 0.004 and health worker support p = 0.031. While the dominant factor influencing compliance with taking medication in elderly people with hypertension is family support p = 0.004 with Exp (B) 90.993. The conclusion of this study is that there is an influence of knowledge, motivation, family support, health worker support and those that do not affect the length of suffering from hypertension and affordability of access to health services. The dominant factor, namely family support, influences compliance with taking medication in elderly people with hypertension in the Salak Health Center Working Area, Salak District, Pakpak Bharat Regency. It is suggested that the Salak Health Center is expected to be taken into consideration and input for the health center to be active in field counseling activities and use social media as a promotional medium, conduct home visits to patients' homes in an effort to monitor compliance with taking medication in order to increase the acceleration of healing of hypertension in the elderly, so as to improve health status in the elderly.